PENGARUH EARNING PER SHARE, RETURN ON EQUITY, DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP HARGA SAHAM DI PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Sangadah, Zuna Mangzilatus; Erdkhadifa, Rendra (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
The study aims to determine the effect of Earning Per Share, Return On Equity, Debt To Equity Ratio and Current Ratio on stock prices in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research method uses an associative quantitative approach. The sampling technique used was purposive sampling, thus finding 17 food and beverage companies listed on the Indonesia Stock Exchange from 2017-2021 as research samples. The data that has been collected is then tested using Eviews, namely testing several tests which include, descriptive statistical test, multicollinearity test, panel regression model selection test, panel regression goodness-of-fit test, partial test, simultaneous test, coefficient of determination test, classic assumption test which includes the normality and heteroscedasticity test. The findings of the data in this study show that the variables Earning Per Share, Return on Equity, Debt to Equity Ratio, Current Ratio have a partial and simultaneous effect on stock prices in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period.